2017
DOI: 10.1177/0044118x17736537
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Dating Violence Victimization and Relationship Dissolution

Abstract: We integrate literature on gender and adolescent friendships to examine the association between adolescent dating violence victimization (ADVV) and relationship dissolution. In particular, we test whether ADVV increases the hazard of relationship dissolution among adolescent romances, and whether a number of friendship dynamics alter the association between ADVV and relationship dissolution. Using discrete time event history models from 5,787 romantically involved youth from the National Longitudinal Study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…The results obtained in this study showed that more than two-thirds of the adolescent victims had a firm intention to continue in their abusive relationships, corroborating that physical dating victimization is not by itself the only, nor the main reason that drives young people to end those violent relationships (Katz et al, 2012; Soller et al, 2020). It seems instead, that the stay/leave decision is strongly mediated by the cognitive and contextual factors such as the interpretations of the victims about the assaults and the presence of other simultaneous types of aggression, e.g.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results obtained in this study showed that more than two-thirds of the adolescent victims had a firm intention to continue in their abusive relationships, corroborating that physical dating victimization is not by itself the only, nor the main reason that drives young people to end those violent relationships (Katz et al, 2012; Soller et al, 2020). It seems instead, that the stay/leave decision is strongly mediated by the cognitive and contextual factors such as the interpretations of the victims about the assaults and the presence of other simultaneous types of aggression, e.g.…”
Section: Discussionsupporting
confidence: 73%
“…It is surprising and worrying that, according to recent international studies, 80% of the adolescent and young adult victims of physical dating violence express their conviction to remain in their abusive relationships; many of them even intend to marry their current partner (Copp et al, 2015; Edwards et al, 2012; Katz et al, 2012; Soller et al, 2020). In Spain, data provided by the Government Delegation of Gender Violence (2019) follows the same direction and indicates that the youngest victims, i.e., those under 18 years of age, tend to stay in their violent relationships an average of 3.5 years before either reporting the abuse, going to a specialized care service, or breaking up their relationship.…”
mentioning
confidence: 99%
“…First, the results revealed the existence of victimization in adolescent dating relationships (32.8% of the sample), in line with previous studies that have examined the prevalence of this phenomenon (Viejo et al, 2016;Marcos et al, 2022). This finding is consistent with the need to emphasize that this type of victimization is a serious social and public health problem (Dosil et al, 2022;Soller et al, 2020); which should be addressed in the educational, social and health fields among the younger population, to: a) minimise the mismatch between the perception of objective victimization and subjective victimization; b) reduce violent behaviours in dating relationships; c) raise awareness of the severity of violent behaviours that occur in interpersonal relationships.…”
Section: Discussionsupporting
confidence: 82%
“…Dating violence (DV) is a worldwide serious social and public health problem (Dosil et al, 2022;Soller et al, 2020;Taylor & Mumford, 2016), with a prevalence rate ranging from 23% to 30% (Viejo et al, 2016), despite of victimization rates vary depending on the characteristics of the samples (i.e., gender, age, race/ethnicity, country, measurement instruments) (Exner-Cortens et al, 2021;Shamu et al, 2016). In this regard, in a meta-analytic review, Wincentak et al (2017) found that one in ten adolescents reported victimization in their dating relationship.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with prior work suggesting that even among couples reporting the presence of DV, adolescents report high levels of care, love, and selfdisclosure (Giordano et al, 2010). Previous studies also found that victimization experiences did not predict relationship dissolution among adolescents (Soller et al, 2020;Muñoz-Rivas et al, 2021). The current findings showed that these difficulties are negatively associated with connectedness and suggest that adolescents may opt to remain involved in an unsatisfying relationship to meet social standards and expectations.…”
Section: Implications and Applicationssupporting
confidence: 91%